METHODOLOGY FOR DEVELOPING PSYCHOLOGICAL STABILITY IN EMERGENCY SITUATIONS IN CADETS OF THE ACADEMY OF INTERNAL AFFAIRS - Kadirova Sayyora Madaminovna (Modern American Journals, 2025)
The article examines the issue of developing psychological resilience among cadets of the Academy of Internal Affairs in emergency situations. The decision-making process of cadets under extreme conditions, stress-coping mechanisms, and the influence of psychological factors are analyzed on a scientific basis. The role of pedagogical and psychological methods in fostering psychological resilience, as well as the effectiveness of training sessions, reflective approaches, and simulation exercises, are highlighted. These approaches ensure not only professional training but also personal development of cadets.
Keywords: Academy of Internal Affairs, cadets, emergency situations, psychological resilience, decision-making, methodology.